A cross-sectional study of testosterone deficiency and inflammatory markers in older men - Rotter, Iwona; Ciosek, Żaneta; Syroka, Anna; Ryl, Aleksandra (Frontiers in Endocrinology, 2025)
BackgroundThis cross-sectional study aimed to examine the relationship between total testosterone (TT) levels, the diagnosis of testosterone deficiency syndrome (TDS), and high-sensitivity C-reactive protein (hsCRP) concentrations in aging men. The analysis also included selected hormonal and anthropometric parameters.MethodsSerum hsCRP levels were measured. Additionally, serum levels of TT, estradiol (E2), dehydroepiandrosterone sulfate (DHEA-S), insulin (I), and sex hormone-binding protein (SHBG) were assessed using ELISA. Patients were divided based on the presence or absence of a TDS diagnosis.ResultsIn patients without TDS, no significant correlation was observed between hsCRP levels and other measured variables. However, higher hsCRP levels were associated with an increased BMI, larger waist and hip circumferences, and elevated triglyceride (TAG) levels compared to patients with lower hsCRP concentrations.ConclusionsThe co-occurrence of testosterone deficiency and elevated inflammatory markers such as hsCRP was associated with less favorable metabolic and anthropometric profiles. While causality cannot be inferred from this observational study, the findings suggest a possible link between systemic inflammation and testosterone deficiency in aging men. These associations merit further investigation in longitudinal and mechanistic studies to clarify directionality and underlying biological pathways.